2009
DOI: 10.1186/1471-2407-9-388
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 5-fluorouracil infusion plus long acting octreotide in advanced well-differentiated neuroendocrine carcinomas. A phase II trial of the Piemonte Oncology Network

Abstract: BackgroundWell-differentiated neuroendocrine carcinomas are highly vascularized and may be sensitive to drugs administered on a metronomic schedule that has shown antiangiogenic properties. A phase II study was designed to test the activity of protracted 5-fluorouracil (5FU) infusion plus long-acting release (LAR) octreotide in patients with neuroendocrine carcinoma.MethodsTwenty-nine patients with metastatic or locally advanced well-differentiated neuroendocrine carcinoma were treated with protracted 5FU intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…In this large cohort of Romer et al, median survivals after 177 Lu and 90 Y-DOTA-TOC were 46 and 36 months, respectively. These results are consistent with those found in numerous other trials of PRRT [7][8][9][10][11][12][13][14][15]. In clinical practice, we frequently observe favourable responses with PRRT in patients with symptomatic, progressive disease resistant to all conventional therapy and often despite poor performance status.…”
supporting
confidence: 92%
“…In this large cohort of Romer et al, median survivals after 177 Lu and 90 Y-DOTA-TOC were 46 and 36 months, respectively. These results are consistent with those found in numerous other trials of PRRT [7][8][9][10][11][12][13][14][15]. In clinical practice, we frequently observe favourable responses with PRRT in patients with symptomatic, progressive disease resistant to all conventional therapy and often despite poor performance status.…”
supporting
confidence: 92%
“…By contrast, patients with tumors displaying high proliferative capacity could be considered as best candidates for chemotherapy (Brizzi et al 2009, Turner et al 2010. Our study confirms the results of previous more limited studies that have reported, in 48-88 patients, correlations between SRS uptake and different NEN characteristics, such as good performance status (Krenning et al 1994), presence of a functioning NEN (Taal et al 1996, Stokkel et al 2011, high level of CgA (Kalkner et al 1995, Asnacios et al 2008, Namwongprom et al 2008, Stokkel et al 2011, or low proliferative index (Adams et al 1998, Ezziddin et al 2006.…”
Section: Endocrine-related Cancersupporting
confidence: 81%
“…Metronomic chemotherapy may be an option using temozolomide and/or capecitabine +/- SSA in G2 NET or in SSTR-negative NET, or capecitabine + bevacizumab after failure of other treatments (such as locoregional therapies, IFN-alpha or everolimus) [69,70,71,72]. Given the limited treatment options in bronchial carcinoids, temozolomide is a therapeutic option based on data from small studies [73,74].…”
Section: Systemic Therapymentioning
confidence: 99%